Work engagement, emotional attitude to work and quality of relations in ‘early’ and ‘late’ dual career couples: the mediating role of satisfaction with one’s achievements - Peplińska, Aleksandra; Godlewska-Werner, Dorota (Health psychology report, 2023)
The aim of the present research was to evaluate the relationship between the level of work involvement and emotional attitude to work and the quality of marital relationships of partners in dual career relationships, divided into 'early career' and 'late career' relationships. In addition, the mediating role of satisfaction with one's accomplishments was assessed. The study included 184 dual career couples, where both partners pursued a professional career in a competitive labour market, often performed managerial functions and reconciled their professional roles with parental roles, where 69 were 'early career' relationships and 115 were 'late career' relationships. All subjects in the dual career marriages had higher education; the age of the respondents ranged from 28 to 43 years and all of them had at least one child. With respect to the applied research tools, the AVEM Questionnaire, the Labour-Family Matching Questionnaire, the Matching Marriage Questionnaire (KDM-2) and the Feeling of Happiness Questionnaire were used. The results show a negative impact of the level of professional and emotional work engagement on the quality of marital relations in the relationship; however, the observed trend only refers to the 'late career' relationships. Therefore, it can be concluded that the level of engagement in professional roles at the moment of entering into a relationship is an important moderating factor in these relationships. In addition, it was found that the level of self-satisfaction eliminates this negative relationship. We can say that the level of satisfaction is the mediator of the relationship between involvement in professional roles and the quality of marital relationships. The level of work engagement and emotional attitude toward work affects the quality of personal life and relationships in a couple. However, this impact can vary due to additional variables such as satisfaction with one's own accomplishments and type of relationship.